Moderate alcohol consumption and cognitive risk - Neafsey EJ (Dove Medical Press, 2011)
Edward J Neafsey, Michael A CollinsDepartment of Molecular Pharmacology and Therapeutics, Loyola University Chicago, Stritch School of Medicine, Maywood, IL, USAAbstract: We reviewed 143 papers that described the relationship between moderate drinking of alcohol and some aspect of cognition. Two types of papers were found: (1) those that provided ratios of risk between drinkers and nondrinkers (74 papers in total) and (2) those that, although they did not provide such ratios, allowed cognition in drinkers to be rated as “better,” “no different,” or “worse” than cognition in nondrinkers (69 papers in total). The history of research on moderate drinking and cognition can be divided into two eras: 1977–1997 and 1998–present. Phase I (1977–1997) was the era of neuropsychological evaluation involving mostly young to middle-aged (18–50 years old) subjects. Although initial studies indicated moderate drinking impaired cognition, many later studies failed to confirm this, instead finding no difference in cognition between drinkers and nondrinkers. Phase II (1998–present) was and is the era of mental status exam evaluation involving mostly older (≥55 years old) subjects. These studies overwhelmingly found that moderate drinking either reduced or had no effect on the risk of dementia or cognitive impairment. When all the ratios of risk from all the studies in phase II providing such ratios are entered into a comprehensive meta-analysis, the average ratio of risk for cognitive risk (dementia or cognitive impairment/decline) associated with moderate “social” (not alcoholic) drinking of alcohol is 0.77, with nondrinkers as the reference group. The benefit of moderate drinking applied to all forms of dementia (dementia unspecified, Alzheimer’s disease, and vascular dementia) and to cognitive impairment (low test scores), but no significant benefit against cognitive decline (rate of decline in test scores) was found. Both light and moderate drinking provided a similar benefit, but heavy drinking was associated with nonsignificantly higher cognitive risk for dementia and cognitive impairment. Although the meta-analysis also indicated that wine was better than beer or spirits, this was based on a relatively small number of studies because most studies did not distinguish among these different types of alcohol. Furthermore, a number of the studies that did make the distinction reported no difference among the effects of these different types of alcohol. Therefore, at present this question remains unanswered. Analysis also showed that the presence of the apolipoprotein E epsilon 4 allele eliminated the benefit of moderate drinking. However, this was based on a relatively small number of studies and several other studies have found a beneficial effect of the epsilon e4 allele. Further studies are necessary to settle this question. The benefit of moderate alcohol for cognition was seen in both men and women, although the amount and pattern of drinking is very different between the two sexes. Lastly, the finding of unaffected or significantly reduced cognitive risk in light to moderate drinkers was seen in 14/19 countries for which country-specific ratio data were available, with three of the five remaining countries showing nonsignificant reductions as well. Overall, light to moderate drinking does not appear to impair cognition in younger subjects and actually seems to reduce the risk of dementia and cognitive decline in older subjects.Keywords: Alzheimer’s disease, dementia, drinking